Allergic Contact Dermatitis of the Anogenital Region in Men and Women. Issue 2 (April 2020) - Cheng, Harriet S.; Fernández-Peñas, Pablo
Abstract : Objectives: Allergic contact dermatitis is an uncommon but important cause of skin disease in the anogenital region. Relevant allergens are described in women and less commonly in men. The aim of this study was to describe outcomes of patch testing in men and women presenting with anogenital dermatoses. Materials and Methods: Cases patch tested for anogenital conditions at 2 patch test clinics in Sydney, Australia, from 2002 to 2017 were reviewed. Positive and relevant patch test reactions were recorded. Results: Thirty-seven women and 27 men were included. Dermatitis was the most common diagnosis, followed by psoriasis and lichen sclerosus. Thirty percent had a final diagnosis of allergic contact dermatitis. The most frequent relevant allergens were fragrance mix I (9%), patients own products (9%), Myroxylon pereirae (8%), cocamidopropyl betaine (3%), and benzocaine (3%). Conclusions: The top positive and relevant allergens seen were in concordance with other reports from Australia and the rest of the world. Fragrances and medicaments are common allergens, and it is recommended that products used on anogenital skin be fragrance free. Testing patients own products is imperative.